2014
DOI: 10.1111/jphp.12170
|View full text |Cite
|
Sign up to set email alerts
|

Liquiritigenin exhibits antitumour action in pituitary adenoma cells via Ras/ERKs and ROS-dependent mitochondrial signalling pathways

Abstract: LQ effectively inhibits pituitary adenoma tumour growth and induces cell apoptotic death mainly via Ras/ERKs and ROS-dependent mitochondrial pathways, suggesting that LQ is a potential suppressor of pituitary adenoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…The three plant extracts, the root extracts of Glycyrrhiza glabra , Paeonia lactiflora , and the leaf extract of Eriobotrya japonica possess moderate cytotoxic properties which agrees with published data [27,38,58,59,60]. So do the six PSM [30,31,34,35,36,37,38,39,40,44,46,47], which are major PSM in these TCM plants (Table 2). Only ursolic acid showed IC 50 values below 20 µM.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The three plant extracts, the root extracts of Glycyrrhiza glabra , Paeonia lactiflora , and the leaf extract of Eriobotrya japonica possess moderate cytotoxic properties which agrees with published data [27,38,58,59,60]. So do the six PSM [30,31,34,35,36,37,38,39,40,44,46,47], which are major PSM in these TCM plants (Table 2). Only ursolic acid showed IC 50 values below 20 µM.…”
Section: Discussionsupporting
confidence: 88%
“…18β Glycyrrhetic acid is the aglycone of glycyrrhizic acid; it exhibits anti-malarial and anti-inflammatory effects, and excellent anticancer potential in some cancer cells [33,34,35]. Liquiritigenin, a major flavonoid of G. glabra , possesses antitumor, anti-inflammatory, and neuroprotective effects [36,37]. The flavonoid isoliquiritigenin has antiproliferative ability in cancer cells [38,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen-day LQ treatment suppresses murine H22-xenografted tumor growth in mice [11]. Our separate research indicates that LQ exhibits antitumor action in pituitary adenoma cells via Ras/ERKs and ROS-dependent mitochondrial signaling pathways [12]. However, there are no direct studies related to the cytotoxic effects of LQ on human hepatocellular carcinoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, AtT-20 and GH3 xenograft mice have been used in different studies to explore the sensibility or sensitizing effect to current treatments, chemotherapeutics drugs and radiotherapy in PAs (Zeng et al 2011, Dai et al 2013, Li et al 2014, Lin et al 2015. Indeed, in recent years, mice xenografts have been widely used to characterize the responses to drugs currently prescribed for these pathologies as lanreotide (Ning et al 2009), thiazolidinediones (Mannelli et al 2010), bromocriptine and/or cabergoline (Lin et al 2017) or to alternative therapies such as metformin , histone deacetylase inhibitor SAHA (Lu et al 2017), Liquiritigenin (Wang et al 2014), Triptolide (Li et al 2017) or Bafilomycin A1 (McSheehy et al 2003), which have been shown to exhibit antitumoral roles in these pathologies. Likewise, PAs xenograft models have also been used to characterize the function of different pathways, genes and relevant mutations in several types of PAs, as Fgfr4 in intracranial xenograft mouse models (Ezzat et al 2006, Jalali et al 2016, inactivating mutations of Pit-1 (Roche et al 2012), overexpression of Lrig1 (Cheng et al 2016) or Meg3 (Chunharojrith et al 2015), persistent activation of the Ras/MAPK pathway (Booth et al 2014), antitumoral actions of miR-524-5p (Zhen et al 2017) and role of RSUME in PTTG protein stabilization (Fuertes et al 2018).…”
Section: Models Of Pituitary Tumorsmentioning
confidence: 99%